2018
DOI: 10.1007/s13187-018-1391-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Human Papillomavirus Educational Intervention among Oral Health Professionals

Abstract: This study aims to evaluate the effectiveness of an educational intervention that was designed to increase human papillomavirus (HPV) awareness and knowledge among oral health providers (OHPs). HPV educational lectures and a dental information toolkit on HPV were offered to OHPs in New England in 2016-2017. OHPs included dentists and dental hygienists. Post intervention surveys were distributed 1 month later. A total of 230 participants attended the educational lectures and received the toolkit. Descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“… Author Population Intervention Educational content Outcome Recommendations Pre-/post-intervention survey studies Kumar et al [48] MD, RN, Residents, allied health professionals 20-min training video with clinical vignettes HPV knowledge, vaccine efficacy in adolescent, addressing concerns of vaccine-hesitant parents Improved knowledge (HPV prevalence in males, age-based variation in vaccination response), attitude, and comfort with counselling Even after watching the video, over half of the providers find that HPV’s sexual transmission makes it difficult to discuss and other modalities of training is needed. Clinical vignettes to model helpful counseling strategies is effective Suryadevara et al [49] Healthcare providers, nurses, office staff On-site educational sessions with booklets Vaccine hesitancy, HPV disease and HPV vaccine, role of HPV vaccine in cancer prevention Across six sites, vaccine series completion rates post intervention increased by 12–20% for 11- to 12-year-olds, and from 7–23% for 13- to 18-year old Use of a general cancer prevention education booklet that bundles all 5 cancer prevention topics is effective Stronger recommendations are needed for male adolescents Shukla et al [50] Oral health professionals 2-hr structured presentation Role of HPV in oropharyngeal cancers, HPV vaccinations, and how to recommend Self-reported ↑ interaction with patients about HPV and vaccination (37%), 67% vs. 26% felt prepared in talking about HPV before/after training, greater clarity in their role in educating their patients about HPV, an increase in knowledge about HPV HPV education for oral health professionals is needed Clarifying provider’s role in educating their patients about HPV should be included in educational interventions Berenson et al [46] MD, MS 30-minute structured presentation Unspecified Knowledge scores improved from 8–15 (out of 16) post-intervention Address knowledge gaps in incidence of cervical cancer in Hispanic women Address knowledge gaps in dosing interval and schedule, and age for vaccination. Reiter et al [47] MD, parents, school staff 30-minute structured presentation Prevalence...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Author Population Intervention Educational content Outcome Recommendations Pre-/post-intervention survey studies Kumar et al [48] MD, RN, Residents, allied health professionals 20-min training video with clinical vignettes HPV knowledge, vaccine efficacy in adolescent, addressing concerns of vaccine-hesitant parents Improved knowledge (HPV prevalence in males, age-based variation in vaccination response), attitude, and comfort with counselling Even after watching the video, over half of the providers find that HPV’s sexual transmission makes it difficult to discuss and other modalities of training is needed. Clinical vignettes to model helpful counseling strategies is effective Suryadevara et al [49] Healthcare providers, nurses, office staff On-site educational sessions with booklets Vaccine hesitancy, HPV disease and HPV vaccine, role of HPV vaccine in cancer prevention Across six sites, vaccine series completion rates post intervention increased by 12–20% for 11- to 12-year-olds, and from 7–23% for 13- to 18-year old Use of a general cancer prevention education booklet that bundles all 5 cancer prevention topics is effective Stronger recommendations are needed for male adolescents Shukla et al [50] Oral health professionals 2-hr structured presentation Role of HPV in oropharyngeal cancers, HPV vaccinations, and how to recommend Self-reported ↑ interaction with patients about HPV and vaccination (37%), 67% vs. 26% felt prepared in talking about HPV before/after training, greater clarity in their role in educating their patients about HPV, an increase in knowledge about HPV HPV education for oral health professionals is needed Clarifying provider’s role in educating their patients about HPV should be included in educational interventions Berenson et al [46] MD, MS 30-minute structured presentation Unspecified Knowledge scores improved from 8–15 (out of 16) post-intervention Address knowledge gaps in incidence of cervical cancer in Hispanic women Address knowledge gaps in dosing interval and schedule, and age for vaccination. Reiter et al [47] MD, parents, school staff 30-minute structured presentation Prevalence...…”
Section: Resultsmentioning
confidence: 99%
“…who focused on providers and staff, and Shukla et al . who focused on oral health professionals, both utilized an educational lecture followed by CDC-based information booklet that providers can use to educate and distribute to their patients [49] , [50] . Suryadevara et al .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies utilized a theoretical framework to drive study questions. [22][23][24][25][26] The majority of articles (6) were interested in outcome variables as they related to general patients, 1 of patients and parents, 1 of female patients, and 2 of adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…22,24,27,29 Two studies demonstrated gaps in providers' knowledge about HPV vaccines. 22,24 Specific knowledge deficits included a lack of awareness concerning improvements in the current HPV vaccine protection against an increasing number of target HPV strains, 24 HPV vaccination recommendations by age group, gender or reimbursement method, names of marketed HPV vaccines 24 and the availability Florida-based dentists (n = 17) and dental hygienists (n = 21) Shepperd, 2013 28 Cross-sectional, online survey F, M 929 Florida dentists randomly selected from three regions based on the Agency for Health Care Administration's regional boundary lines Daley, 2014 22 Cross-sectional, online survey F, M 210 Florida-based dentists Hosking, 2017 27 Cross-sectional, in-person survey F, M 64 Attendees from the American Academy of Pediatric Dentistry (AAPD) annual meeting for graduate and associate program directors Thompson, 2017 19 Qualitative, focus groups F 48 National sample of dental hygienists recruited via email Daley, 2018 26 Cross-sectional, in-person survey F, M 182 Dentists (n = 36) and dental hygienists (n = 146) recruited from regional dental conference Kline, 2018 23 Mixed methods: qualitative focus groups and quantitative in-person surveys F, M 284 Dentists (n = 70) recruited from regional conference in Southeastern US and dental hygienists recruited from national conference (n = 214)…”
Section: Knowledgementioning
confidence: 99%
“…HPV education proved to be successful at increasing self-reported knowledge in dental professionals. 26 In the clinical applications regarding HPV-associated cancer and vaccine administration in oral health, students were assessed in two dental schools. The role of oral health professionals and the correlation coefficient regarding knowledge of HPV vaccinations among students was 0.71, and was 0.85 for vaccine administration, clearly illustrating the deficit in knowledge around HPV vaccinations.…”
Section: Preventionmentioning
confidence: 99%